The European Composite Administration Facing the Challenges of Migration - Natalia Kohtamäki (Studia Europejskie, 2021)
In classical theoretical refl ections on international reality, one of the leading paradigms is the belief that the Westphalian order based on sovereign states has evolved into a diverse network of interdependent actors. From a legal perspective, a network such as this has the character of multi-level normative linkages. Legislation with varying degrees of impact in terms of its binding force is enacted within a number of parallel consultative bodies. Within the EU this network takes on a concretised, institutional normative dimension, the so-called European Composite Administration which is evident in specifi c areas such as cyber security, asylum and migration policies, energy, and fi nancial market regulation. In the European Union, decentralised agencies play a leading role in a such compound bureaucracy. They are one of the main instruments in the European system for harmonising regulation and practices in specific areas of EU activity. In a crisis situation there is an increasing tendency to modify their powers. Within the European Composite Administration, bodies such as EASO, the agency responsible for migration and asylum policies, play a key coordinating role between the Member States. The crisis legitimises institutional changes, by expanding the catalogue of regulatory agencies’ competencies. While practitioners, especially in individual offices in the Member States, may find such processes acceptable in relation to the ideal of efficient and effective administration, these phenomena may be regarded as worrying from the point of view of control over a growing complex integrated administrative apparatus.